Expansion of the biocontrol spectrum of foliar diseases in rice with combinations of rhizobacteria (Revista Ciência Agronômica, 2017)
The cultivation of irrigated rice is subject to the occurrence of various diseases, where damage causes losses inproductivity. Alternatives are currently being sought to control these diseases, with biocontrol a viable possibility. With the aimof broadening the spectrum of action of biocontrol, this study evaluated the effect of combinations of biocontrol bacteria on riceblast (Pyricularia grisea), brown spot (Bipolaris oryzae) and leaf scald (Gerlachia oryzae) in rice plants. The effect of isolatecombinations was assessed by microbiolization of seeds from the rice cultivar El Paso L144 with suspensions of the bacteriaDFs185 (Pseudomonas synxantha), DFs223 (P. fluorescens), DFs306 (unidentified), DFs416 and DFs418 (Bacillus sp.), usedindividually or in a combination of two, three or four compatible isolates. Seeds treated with Carboxin Thiram fungicide (T+F)at a final dosage corresponding to 3 ml kg-1 were used as control. Considering the leaf diseases together, eight treatmentssignificantly controlled all three diseases, and were superior to the treatment with fungicide. Among these treatments, sevenwere combinations. Only the DFs306 bacteria were able to control the three diseases when used individually. It can thereforebe presumed that combinations of bacteria, when microbiolized in rice seeds, can broaden the spectrum of action for the controlof rice blast, brown spot and leaf scald.